Peculiarities of the Dynamics of Volume of Credits Granted by the Ukrainian Banking System to Residents - Pogorelenko Nataliya P. (Problemi Ekonomiki, 2015)
Any questions related to crediting processes are constantly in the focus of attention. At that analyzing the dynamics of volume of the granted credits acquires a special role, as it determines movement of outgoing financial flows both of individual banks and the banking system in terms of stability of the banking system, individual banks and economic development in general. The purpose of the article is to analyze the movement of credit flows of the domestic banking system both with relation to the selected time period and for individual intervals during this time period. With the help of wavelet analysis local peculiarities of the studied time series have been identified due to decomposition of the incoming data into two sets of data, one of which is determined by a set of approximation coefficients, and the other — by that of detail ones. Approximation coefficients generalize the trend characteristics of the studied time series and detail coefficients reveal the existing peculiarities of the studied time series. The wavelet transform as a part of wavelet analysis permitted to build a hierarchical structure of the incoming studied time series, which increased the possibility of carrying out a more detailed analysis of the studied time series. Using wavelet analysis allows specifying periods of correlation and decorrelation between individual series of the analyzed data. It permits to draw conclusions about justifying adjustments of dynamics of components in the general series of the credit volume granted to residents and create a balanced policy of the impact on the banking system activity. The subject of the further research is developing recommendations on regulation of banking activities based on wavelet analysis.